Comparative Analysis of Digital Currency Regulations: International and Domestic Legal Frameworks - Al Nabhani, Anfaal Said Hamdoon; Al Masoudi, Rayan Saleh Suleiman; Abdel-Gadir, Sufian (Journal of Ecohumanism, 2025)
This study conducts a comparative analysis of digital currency regulations, focusing on international and domestic legal frameworks, with a case study of Oman. The research explores the global regulatory landscape, highlighting approaches in jurisdictions such as the United States, the European Union, and Gulf Cooperation Council (GCC) countries. It emphasizes the economic, social, and technological drivers necessitating comprehensive digital currency regulation and identifies challenges, including financial instability, consumer risks, and regulatory ambiguity. By examining diverse regulatory models, the paper underscores the critical need for balance between fostering innovation and mitigating risks associated with digital currencies. The study investigates the legal and technical gaps in Oman’s current regulatory environment and compares them with global best practices. It also discusses the potential benefits of adopting Central Bank Digital Currencies (CBDCs) to enhance financial inclusion and monetary control. The findings reveal that while many advanced economies embrace digital currencies with robust regulatory measures, GCC countries, including Oman, exhibit cautious and varied stances, reflecting regional and societal complexities. The research employs descriptive and analytical methodologies to assess legislative developments and the implications of digital currency transactions. The paper concludes that comprehensive, flexible, and internationally coordinated regulatory frameworks are essential to address the challenges posed by digital currencies while leveraging their potential for economic development. Recommendations include fostering global cooperation, enhancing public awareness, and developing specialized regulatory bodies to oversee digital currency markets effectively. This study provides valuable insights for policymakers, legal experts, and financial institutions striving to navigate the rapidly evolving digital currency ecosystem.